To be Enchanted or Enchanting? A Fairytale Reproduced - ERTANTI, Amaliyah (2013)
This research entitled "To be Enchanted or Enchanting: A Fairytale Reproduced" focuses on examining the ways in which Levine's "Ella Enchanted" present a reproduced version of "Cinderella" tales. The framework of feminist literary criticism and subjectivity by Trites (1997) is used to analyze the research. The research employs a textual analysis approach in which the writer describes, interprets, and analyzes the text to answer the problem of the research. The ways of Levine's "Ella Enchanted" reproduce the retelling of classic fairytale "Cinderella" is depicted mainly from different characteristics of the main female character which are rebellious, active, determined, powerful, brave, intelligent, assertive, and independent. Moreover, the magical element in "Ella Enchanted" serves a different role that marks Ella's effort in breaking her curse rather than helping her in gaining fortune as other characters in most fairytale do. Afterward, the fairytale plot of "Ella Enchanted" explains the character's sequence actions in gaining her power and the way she finally achieves her liberation. Through the plot, Ella as the heroine mostly acts as the holder of authority in deciding her own action although she is in the condition of being cursed. The intertextual connection explains the functions of intertextuality in "Ella Enchanted" and notes the cultural shift which helps the readers to see the different attitude of main female characters in dealing with their ordeal. Finally, the research presents the main female character with subjectivity that is portrayed through the deconstruction of the female stereotypes in fairytales.